Effectiveness of Problem-Based Learning Model on Cognitive Learning Outcomes and Science Self-Efficacy (SSE) - Marsha Hemalia Putri; Nailil Inayah; Aning Wida Yanti; Rizka Novia Rochmawati (Jurnal Studi Guru dan Pembelajaran, 2026)
Students’ cognitive learning outcomes and Science Self-Efficacy (SSE) are important factors influencing success in science learning. However, many students still demonstrate low confidence and limited understanding of Ecology, indicating the need for innovative learning models. This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model on cognitive learning outcomes and students' SSE in Ecology at the junior high school level. This study employed a quantitative approach with a one-group posttest-only design. The population consisted of seventh-grade students at Sekolah Indonesia Jeddah (SIJ), Saudi Arabia. Using simple random sampling, 22 students from class VII B were selected as the research sample. Data were collected using test and non-test instruments, namely an essay test to measure cognitive learning outcomes and a Science Self-Efficacy (SSE) questionnaire. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test as a prerequisite test, and a one-sample t-test for hypothesis testing. The results showed that the average score for students' cognitive learning outcomes was 89.59, and the average score for SSE was 84.86, with both distributions normal (Sig. > 0.05). The t-test results (Sig. = 0.000 < 0.05) showed that applying the PBL model significantly improved students' cognitive learning outcomes and SSE. The highest cognitive indicator was found in C6 (create), at 92.4%, followed by C5 (evaluate), at 73.4%. In addition, the most dominant dimension of SSE is Magnitude at 75%. The results of this study indicate that the PBL model is effective on students' cognitive learning outcomes and SSE in Ecology material.